A SECURITIZAÇÃO DA FRONTEIRA CORUMBÁ-MS/BRA – PUERTO QUIJARRO-BO: ANÁLISE DAS PERCEPÇÕES SOCIAIS - THAIS DA SILVA ALPIRES (2022)
In the latest "Global Trends Report", published by the United Nations High Commissioner for Refugees (UNHCR) presenting on June 18, 2021, the data shows that by the end of 2020, about 82.40 million people were forcibly displaced from their homes, motivated by Issues of Grave and Widespread Human Rights Violations. The publication of the data precedes World Refugee Day on June 20, in the perspective of demonstrating the increase in the flow of migration, and that it requires challenging management to all countries. The response of countries varies in opening or closing their borders. The application of restrictive policies results in irregular migration, due to the immigrant's difficulty in complying with all the requirements issued by the states' tax agencies. The irregularity results in extreme vulnerability and precedes discriminatory actions by Brazilian citizens, against a supposed fraud in the country's legal apparatus, practiced by the immigrants. In view of the increasing volume of immigration, caused by persecutions, human rights violations or even situations of serious disturbance in the local public order, this paper explores the perception of the public opinion of Brazilians about immigrants in the city of Corumbá-MS. Previous research has revealed a significant difficulty in integrating groups of international migrants in the Pantanal municipality, due to preconceptions based on securitist discourses. This dissertation identifies points of securitization practices, based on the analysis of border control actions and measures. The hypothetical deductive method of analysis is used, whose procedure is a case study of the city of Corumbá. The methodology used includes a form elaborated by the Google Form platform, sent to Brazilian residents of the city. The dissertation is organized into three chapters: the first corresponds to a presentation of the theoretical aspects that guide the debate, reflections on Contemporary Migrations and the study of Securitization. The second brings study for borders, International Relations and Geopolitics; and the main actions established in the border areas, which constitute measures to securitize the areas, focusing on the border between Corumbá-MS–Puerto Quijarro-BO. And the third analyzes the data obtained by the interview form, for discussion and compilation of the information. In summary, the work gathers material in which the borders are spaces for strengthening the imposition of the legitimate use of force by the states, migration as a problem of national security, and the immigrant as a target of discriminatory actions.